China's drug practices and policies: regulating controlled substances in a global context - Lu, Hong (Ashgate Pub, 2009)
The consumption and control of illegal substances -- Social conditions and opium in Imperial China before 1911 -- Drug law and it context in the republic era -- Narcotics control in the People's Republic of China -- Theoretical explanations of the drug laws